PENERAPAN DRIFT SPEKTRA DALAM PERANCANGAN STRUKTUR TAHAN GEMPA - P.Sianturi, Dedy
Abstract : This research discusses the applications of drift spectrum method in analyzing interstorey structure drift which modeled by 5, 10 and 15 stories structures. Drift spectrum method uses the traveling wave equations on continuous shear-beam model. Analysis that used on drift spectrum is elastic analysis. The results are compared with response spectrum method and structural analysis programme. These comparisons show the acceptable differences, so this drift spectrum method reliable to analyze structure response on dynamic loads. This research also shows the useful and the weakness of the drift spectrum method. The useful of this drift spectrum method are the minimum number of parameters (structure period, total structure height, the fraction of critical damping, ground velocity and displacement as dynamic loads), simple data computation and presents interstorey drift more detail. Disability on in-elastic analysis shows the weakness of this drift spectrum method, which in-elastic analysis is an important thing on seismic design.